Beak & Ally. 2, Bedtime jitters - Feuti, Norman (New York, New York : Harper Alley, an imprint of HarperCollinsPublishers, 2021)
With weird swamp noises swirling around him, Beak the Bird can't get any sleep until his friend Ally the alligator shows him where the racket is coming from.
Keywords: Alligators -- Comic books, strips, etc; Birds -- Comic books, strips, etc; Best friends -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Bedtime -- Comic books, strips, etc; Noise -- Comic books, strips, etc; Alligators -- Fiction; Birds -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Bedtime -- Fiction; Noise -- Fiction; Cartoons and comics; Humorous comics; Funny animal comics; Graphic novels